A comprehensive genomic and transcriptomic analysis of dimorphic human pathogen fungi and its relation with virulence. (2018)
The ascomycete order Onygenales includes most dimorphic fungi that are pathogenic to humans. The most virulent of these fungal pathogens are found in the genera Paracoccidioides, Histoplasma, Blastomyces (family Ajellomycetaceae) and Coccidioides, which all have special medical relevance for South and/or North America. Paracoccidioides brasiliensis is endemic in Latin America where it is the third leading cause of death from chronic infection in particular countries and Histoplasma capsulatum is endemic in the United States where it is the most common cause of fungal respiratory infections in healthy individuals. These organisms share a close evolutionary relationship and common strategies of pathogenesis. However, despite the high incidence of infection with thermally dimorphic fungi, there is little understood about the molecular virulence mechanisms utilized by these organisms to manipulate disease progression in the host. A central line of research on Paracoccidioides, Histoplasma and other dimorphic human pathogenic fungi at the genome and gene level is the identification and characterization of virulence factors or molecular traits that make this fungus pathogenic and could be used as a lead for the design of vaccines, drugs and diagnostic methods. Sequencing of genomes and transcriptomes and subsequent comparative analysis is a particularly straightforward way to exhaustively scan and characterize species or individual strains of interest for this purpose. We propose to approach these endemic pathogens from an advanced and previously tested comparative genomics and transcriptomics framework. Two very recent advances make this an opportune moment to fill the remaining knowledge gap in a systematic way. The first is that next-generation sequencing has become inexpensive, and now it is more attractive to sequence the genomes of multiple isolates (population DNAseq) or the transcriptomes of multiple conditions (RNAseq) both allowing comparative analysis. The second is that for the Ajellomycetaceae family there are now several references genomes of the dimorphic pathogens Paracoccidioides, Histoplasma and Blastomyces and also genomes from non or less pathogenic species from the same family comprising Emmonsia parva, E. crescens, E. pasteuriana, Spiromastix grisea and Polytolypa hystricis. Part of those genomes were assembled, annotated and analyzed by our group in collaboration with the Broad Institute in previous and current projects allowing us to obtain the know-how for genome-based studies. Both recent advances showed that is a perfect moment for our group to continue this avenue of comparative genomics and functional genomics on the dimorphic pathogenic fungi Paracoccidioides and Histoplasma, including strategies such as RNAseq and transcriptional profiling. Here we propose to sequence the genomes (DNAseq) of isolates with particular phenotypic and geographic location as well as transcriptomes (RNAseq) of reference strains of P. brasiliensis and H. capsulatum in a comparative population and functional genomics approach. By performing genome and transcriptome based studies we expected to achieve success in this multi-target project allowing us: 1) to update and to improve the reference genome assemblies and annotations of Paracoccidioides and Histoplasma; 2) to identify differential molecular traits and mechanisms related to the pathogenesis and virulence of H. capsulatum and P. brasiliensis via comparative genomics (gene gain/losses, family expansion/contractions, etc) with other closely related pathogens and non-pathogens of the Ajellomycetaceae family, and via population genomics analysis within isolates of the same species with particular interesting phenotypes, source or location (SNPs analysis, recombination analysis, selection analysis) and 3) to identify differentially transcribed genes between host simulated and non-host condition that could be related with fungal virulence and pathogenicity.